2023
DOI: 10.1029/2022gh000704
|View full text |Cite
|
Sign up to set email alerts
|

Radon Dynamics and Effective Dose Estimation in a Touristic Volcanic Cave: La Cueva del Viento, Tenerife (Canary Islands, Spain)

Abstract: La Cueva del Viento is a volcanic lava tube located in Tenerife Island (Canary Islands, Spain). Its touristic section, 180 m long, receives more than 28,200 visitants each year. According to the European and Spanish legislation, a radon monitoring program is required to minimize the radon exposition of workers, tourists, and cavers. In this work, we studied the radon concentration dynamics in the touristic section of the cave for ca. 1 year, using both passive and active radon detectors. Pluviometry and extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The study noted how changes, such as the installation of a second closure, drastically reduced the connection between cave chambers, indicating the long-term impact of human intervention on cave environments. Most recently, Salazar-Carballo et al (2022) examined the radon concentration dynamics in La Cueva del Viento, a volcanic lava tube in Tenerife Island [135]. The study found that rain and external air temperature significantly influenced the seasonal and daily variations in indoor radon concentrations.…”
Section: Countrymentioning
confidence: 99%
“…The study noted how changes, such as the installation of a second closure, drastically reduced the connection between cave chambers, indicating the long-term impact of human intervention on cave environments. Most recently, Salazar-Carballo et al (2022) examined the radon concentration dynamics in La Cueva del Viento, a volcanic lava tube in Tenerife Island [135]. The study found that rain and external air temperature significantly influenced the seasonal and daily variations in indoor radon concentrations.…”
Section: Countrymentioning
confidence: 99%
“…Typically, passive solid state nuclear track detectors (SSNTDs) are used for this type of long-term research, or active ones to observe changes in concentrations in the short and medium terms [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these advantages, MNPs have been successfully implemented in multiple areas such as energy and data storage [19,20], biosensing [21], catalysis [22], bioremediation [23], neural stimulation [24], pharmacological liberation [25,26], cancer treatment [27] and clinical diagnosis [14,28]. As mentioned above, the use of magnetic sorbents significantly simplifies sample manipulation by isolating the target by applying an external magnetic field [29,30].…”
mentioning
confidence: 99%